Zeitschrift für Sozialreform : Journal of Social Policy Research (De Gruyter Oldenbourg, 1983)
The Zeitschrift für Sozialreform is an academic journal that encompasses the entire field of research on the social state and social policy in the social sciences, economics, and legal scholarship. It is aimed at academics and social policy actors.